New Media as a Tool for Menstruation Hygiene Awareness: A Systematic Review - Thakur, Sarima; Suri, Chanchal Sachdeva; Dosajh, Babita; Amika, Amika; Grover, Namita (Journal of Neonatal Surgery, 2025)
In recent years, new media has emerged as a powerful tool for raising awareness about menstruation hygiene and breaking taboos. This systematic review explores the impact and effectiveness of various new media platforms in promoting menstruation hygiene awareness, such as social media, mobile applications, and online forums. Through a comprehensive analysis of studies conducted between 2010 and 2024, this review highlights the transformative role of digital platforms in disseminating information and empowering individuals with knowledge about menstrual health. The findings suggest that social media campaigns, interactive apps, and online educational content have significantly improved menstrual hygiene practices among diverse populations. Social media campaigns leverage the widespread reach of platforms like Facebook, Instagram, and Twitter to disseminate information quickly and engage with a broad audience. Interactive apps offer personalized education and reminders, making it easier for users to track their menstrual health and receive tailored advice. These platforms not only provide accurate information but also create supportive communities where individuals can share experiences and seek advice without fear of stigma. The anonymity and accessibility of online forums and social media groups allow for open discussions that might not occur in face-to-face settings. This communal support is crucial in breaking down societal taboos and empowering individuals to take control of their menstrual health. Additionally, the review identifies the challenges and limitations of using new media for this purpose, including issues related to digital literacy, accessibility, and the potential for misinformation. Digital literacy is essential for effectively using these platforms, and there is a risk for those with limited access to technology. This review underscores the potential of new media to revolutionize menstruation hygiene education and advocacy. The insights gained from this review can inform future initiatives and guide policymakers, educators, and health professionals in harnessing the power of new media to address menstruation hygiene effectively...